Place segmental massage in physical rehabilitation of patients with chronic bronchitis. - Sitnikova N.S; Kamenevа M.J (Kharkov National Pedagogical University, 2011)
The place of segmental massage as one of the most important methods of physical rehabilitation for patients with chronic bronchitis is shown. The principles of treatment of patients with chronic bronchitis at the sanatorium stage were defined. The proposed method of segmental massage based on the principles of domestic and foreign doctors and rehabilitators. Proved that when used properly, segmental massage in patients with increased efficiency, activated natural systems to adapt, improve the state of the central and autonomic nervous system, stimulates mental activity, stops coughing and begins recovery.